Honduras : First Reviews Under the Stand-By Arrangement and the Arrangement Under the Standby Credit Facility, and Request for Modification of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Honduras. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2019)
This paper highlights Honduras' First Reviews Under the Stand-By Arrangement and the Arrangement Under the Stand-By Credit Facility, and Request for Modification of Performance Criteria. Despite headwinds to growth and a challenging external environment, the Honduran authorities remain fully committed to the economic program supported by the IMF. They have maintained prudent macroeconomic policies-the fiscal position is in line with the Fiscal Responsibility Law, inflation is within the central bank's target band, and the current account deficit has narrowed despite adverse terms of trade-and have taken initial steps on structural reforms to promote sustained, inclusive growth. Important measures to strengthen the governance and anti-corruption frameworks have been incorporated into the program, adding to the ongoing efforts to strengthen the institutional framework in the central bank and in public finances, and to improve the business environment. The authorities are expected to protect the revenue mobilization efforts made over the past years to reduce the infrastructure gap and increase social spending. These efforts seem to be critical to reduce poverty and inequality, while maintaining a prudent fiscal position that secures debt sustainability over the medium term.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet